Problems of development of project management in the system of public administration of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
This article discusses the need and prerequisites for the introduction of a project management systemin state authorities. The relevance of project management is due to new challenges to the systemof public administration in the Republic of Kazakhstan. In the contemporary conditions, the importanceof the ability of state bodies to implement the planned projects on time and within the framework ofthe budgeted budgets is increased. It is also necessary to distinguish project activities from the overallactivities of the organization. For this purpose, the article identifies the similarities between the processand project activities, identifies the main advantages from the implementation of the project approachin public administration, examined the status and main directions for the promotion of project managementin public administration in the Republic of Kazakhstan. The international experience of projectmanagement is considered and on the basis of them the ways of development of the project approachin the public sector of Kazakhstan.